2014
DOI: 10.1002/acr.22358
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Juvenile Dermatomyositis: Exposure to Tobacco and Air Pollutants During Pregnancy

Abstract: Objective. To evaluate the influence of exposure to inhaled environmental factors during pregnancy on the diagnosis of juvenile dermatomyositis (DM).Methods. We performed a case-control study comprising 20 juvenile DM patients and 56 healthy controls matched by age and sex who were residents in the metropolitan region of a large city. A questionnaire assessed demographic data and environmental inhalation exposure during pregnancy (occupational exposure to demolition, chalk, construction and/or quarry dust, pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 14 publications
0
20
1
2
Order By: Relevance
“…Just as peak incidence of RA varies with age, there may be periods of life where the impact of air pollutants has greater influence on subsequent susceptibility to developing autoimmune diseases. Just as younger patients appeared to be more vulnerable to an association between air pollutants and JIA onset in Zeft et al's study [23], using multivariate analysis controlling for smoking, occupational exposure, home distance to sources of inhaled pollutants, seasonality, and traffic exposure, Orione et al showed a significant association (odds ratio of 12.2) between carbon monoxide in the third trimester and the subsequent development of juvenile dermatomyositis [28]. Interactions between pollution exposure and specific risk alleles for different autoimmune conditions may also explain the difference in findings of association between air pollutants and different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Just as peak incidence of RA varies with age, there may be periods of life where the impact of air pollutants has greater influence on subsequent susceptibility to developing autoimmune diseases. Just as younger patients appeared to be more vulnerable to an association between air pollutants and JIA onset in Zeft et al's study [23], using multivariate analysis controlling for smoking, occupational exposure, home distance to sources of inhaled pollutants, seasonality, and traffic exposure, Orione et al showed a significant association (odds ratio of 12.2) between carbon monoxide in the third trimester and the subsequent development of juvenile dermatomyositis [28]. Interactions between pollution exposure and specific risk alleles for different autoimmune conditions may also explain the difference in findings of association between air pollutants and different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies found associations between pollution and birth weight [24][25][26][27][28] . Medeiros et al 22 observed in their study that the maternal exposure in the first pregnancy trimester to air pollution may contribute to lower gain of weight of the child at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Important contributors include point sources, which denote emissions from larger, stationary industrial and commercial facilities, on-road sources, produced by vehicles on roads, and secondary sources, which are formed from the chemical reactions of other emitted pollutants (22). Since DM has been associated with airborne pollutants, this dataset may be useful in analyzing exposure patterns (1113).…”
Section: Introductionmentioning
confidence: 99%